Tectonic Tremor Explained by Successive Ruptures of Clustered Quartz‐Filled Shear Veins - S. Yabe; K. Ujiie (Geophysical Research Letters)
Abstract A tectonic tremor is a successive seismic signal observed along plate boundaries in subduction zones. However, the source processes and mechanisms responsible for the tremor remain unclear. Quartz‐filled shear and extension veins are clustered in tens to hundreds of meters thick subduction shear zones exhumed from deep tremor source regions and record repeated brittle low‐angle thrust shear and tensile failure at near‐lithostatic fluid pressures. Seismic wave radiation from clustered quartz veins was modeled using a probabilistic cell automaton model. The results show that successive ruptures of clustered veins are capable of radiating seismic waves with consistent sizes of the seismologically observed tremor and very low‐frequency earthquake (VLFE) and that shear veins should be dominant over extension veins to explain the low‐angle thrust focal mechanisms of VLFE. We propose that tremor signals are primarily attributable to successive shear slip along shear veins in a finite‐thickness shear zone.